Dynamic Transmission of Dengue Hemorraghic Fever and Climate Variability Patterns in Depok and Bogor (Indian Journal of Public Health Research & Development, 2020)
Dengue hemorrhagic fever (DHF) has become an endemic in major cities in Indonesia. Climate change, andpoor level of awareness and knowledge of the community in Indonesia causes the case of DHF to continueto exist and it tends to increase. In the extraordinary events in 2015 the morbidity rate reached 50.75. TheIntergovernmental Panel on Climate Change (IPCC) prediction in 1996 stated that the incidence of denguehemorrhagic fever in Indonesia will increase threefold from 2070, if the environment and communityconditions do not change. This study aims to produce a system dynamics model with ecological analysis todetermine the dynamics of the DHF incidence with climate variability patterns in Depok and Bogor. The designof this study is ecologic study with hypothesis test, modeling, simulation, and intervention. Interviews withrespondents include the level of knowledge, attitudes, and behavior (PSP) of the community. Measurementof climate factor includes rainfall, temperature, humidity, and CO2 level in the ambient environment. Theresults of DHF system dynamics model simulation show the program intervention scenario that has themost significant effect on the decline of Breeding Places and the decrease of DHF cases by increasing theparticipation of the community to actively control water places that are potential for mosquito breedingplaces.
Keywords: system dynamics model, intervention, simulation, dengue hemorrhagic fever, climate change